Overcoming treatment gaps in the management of depression with non-pharmacological adjunctive strategies - Purebl, György; Schnitzspahn, Katharina; Zsák, Éva (Frontiers in Psychiatry, 2023)
There is considerable evidence that simple, cost-effective, non-pharmaceutical strategies can be readily implemented to improve outcomes in the treatment of depression. It is estimated that 4.4% of the world's population suffers from depression. Despite being a major public health concern and the availability of both pharmacological and non-pharmacological treatments, many depressed people remain undiagnosed and receive no or inappropriate treatment. Several possible underlying factor of treatment gap can be identified in relation to pharmacotherapy and psychotherapy of depression, including side effects, partial remission, treatment-resistant depression and the limited availability of psychotherapy. In addition to developing new therapeutic options, much more could be done to optimise the use of existing therapies, including combining available drug treatments with quick, simple and cost-effective non-pharmacological methods: low-intensity psychological interventions, online self-help tools and lifestyle medicine. In addition to increasing the effectiveness of treatments, prevention is equally important: awareness programs to further reduce the treatment gap, and community dissemination of the life skills that help maintain positive mental health.